comparison of free radicals scavenging activity, phenolics levels and antibacterial activities by iraq propolis from different sources - Ghassan M. Sulaiman; Zeid Abdul-Majid Nima (مجلة بغداد للعلوم)
propolis (bee glue) a resinous material derived by bees from many plant sources was known for its therapeutic properties.